2013
DOI: 10.1016/j.yjmcc.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic ethanol consumption increases cardiomyocyte fatty acid uptake and decreases ventricular contractile function in C57BL/6J mice

Abstract: Alcohol, a major cause of human cardiomyopathy, decreases cardiac contractility in both animals and man. However, key features of alcohol-related human heart disease are not consistently reproduced in animal models. Accordingly, we studied cardiac histology, contractile function, cardiomyocyte long chain fatty acid (LCFA) uptake, and gene expression in male C57BL/6J mice consuming 0, 10, 14, or 18% ethanol in drinking water for 3 months. At sacrifice, all EtOH groups had mildly decreased body and increased hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 69 publications
(102 reference statements)
3
36
1
2
Order By: Relevance
“…In the present study, myocardial changes were found in the chronic alcohol-fed mice, such as fatty acid accumulation, cardiomyocyte vacuolization, myocardial myofibril loss and disarray, sarcoplasmic reticulum edema, and swollen disrupted mitochondria, which are consistent with those of previous reports [31-33]. The mechanisms underlying ACM include oxidative stress [4, 5], impaired mitochondrial bioenergetics [2], and derangements in fatty acid metabolism and transport [6]. Our observations in the alcohol-treated mice using light and electron microscopy are in line with those seen in postmortem myocardial biopsies from human subjects with ACM [22, 34], even though we have no evidence that our mice developed dilated cardiomyopathy (DCM).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, myocardial changes were found in the chronic alcohol-fed mice, such as fatty acid accumulation, cardiomyocyte vacuolization, myocardial myofibril loss and disarray, sarcoplasmic reticulum edema, and swollen disrupted mitochondria, which are consistent with those of previous reports [31-33]. The mechanisms underlying ACM include oxidative stress [4, 5], impaired mitochondrial bioenergetics [2], and derangements in fatty acid metabolism and transport [6]. Our observations in the alcohol-treated mice using light and electron microscopy are in line with those seen in postmortem myocardial biopsies from human subjects with ACM [22, 34], even though we have no evidence that our mice developed dilated cardiomyopathy (DCM).…”
Section: Discussionsupporting
confidence: 90%
“…Chronic alcohol consumption leads to a number of alterations in the metabolic function of the heart [2, 23] and results in a deterioration of heart function [6, 24-26], which is a leading cause of cardiomyopathy. The exact amount and duration of alcohol consumption associated with the development of ACM is humans are variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…При ЭХОКГ было выявлено снижение фракции выброса левого желу-дочка (ЛЖ), которое отрицательно коррелировало с уровнем триглицеридов. Снижение экспрессии коак-тиватора гамма-рецепторов, активируемых проли-фераторами пероксисом (PGC-1α) и его таргетных ге-нов, привело к снижению уровня сердечной АТФ, что, в свою очередь, вызывает нарушение сократи-тельной функции миокарда, вызванной хроническим употреблением алкоголя [34].…”
Section: развитие алкогольной кардиомиопатииunclassified
“…Подобно другим дилатационным КМП, алкогольная характеризуется дилатацией (рас-ширением) ЛЖ, истончением стенок миокарда, нару-шением его сократительной функции, при этом отсут-ствуют заболевания коронарных артерий либо дефи-цит питательных веществ [34,35].…”
Section: развитие алкогольной кардиомиопатииunclassified